![image](https://tex.z-dn.net/?f=9%5E%7Bx%7D++%2B+2+%5Ctimes+12+%5E%7Bx%7D++-+3+%5Ctimes++%7B16%7D%5E%7Bx%7D++%3D+0+%5C%5C++%5C%5C++%7B3%7D%5E%7B2x%7D+%2B+2+%5Ctimes+%7B3%7D%5E%7Bx%7D+++%5Ctimes++%7B4%7D%5E%7Bx%7D++-+3+%5Ctimes++%7B4%7D%5E%7B2x%7D++%3D+0++%5C%3A++%5C%3A++%7C+%3A+%7B4%7D%5E%7B2x%7D+++%5C%5C++%5C%5C++%28%5Cfrac%7B3%7D%7B4%7D+%29+%5E%7B2x%7D++%2B+2+%5Ctimes++%28%5Cfrac%7B3%7D%7B4%7D+%29+%5E%7Bx%7D++-+3+%3D+0+%5C%5C++%5C%5C++%28%5Cfrac%7B3%7D%7B4%7D+%29+%5E%7Bx%7D+%3D+t%2C++%5C%3A+t+%3E+0+%5C%5C++%5C%5C++%7Bt%7D%5E%7B2%7D++%2B+2t+-+3+%3D+0+%5C%3A+)
0 \\ \\ {t}^{2} + 2t - 3 = 0 \: " alt="9^{x} + 2 \times 12 ^{x} - 3 \times {16}^{x} = 0 \\ \\ {3}^{2x} + 2 \times {3}^{x} \times {4}^{x} - 3 \times {4}^{2x} = 0 \: \: | : {4}^{2x} \\ \\ (\frac{3}{4} ) ^{2x} + 2 \times (\frac{3}{4} ) ^{x} - 3 = 0 \\ \\ (\frac{3}{4} ) ^{x} = t, \: t > 0 \\ \\ {t}^{2} + 2t - 3 = 0 \: " align="absmiddle" class="latex-formula">
t=-3 — не удовлетворяет условию t>0
t=1
Ответ: 0